OPTIMALISASI PERAN KADER MELALUI PROGRAM INOVASI TUNA (TELUR UNTUK ANAK) DALAM PEMANFAATAN PROTEIN HEWANI GUNA MENURUNKAN ANGKA STUNTING DI DESA GRATI, KECAMATAN SUMBERSUKO, KABUPATEN LUMAJANG - Sulton Wariin; DANIAR FARADINA; AI NUR ZANNAH (LPPM Universitas dr. Soebandi, 2026)
Stunting remains a significant public health problem, particularly in rural areas, influenced by low animal protein nutritional intake and limited knowledge of health cadres as the spearhead of community services. Grati Village, Sumbersuko District, Lumajang Regency, is one area that requires strengthening the role of cadres in stunting prevention efforts. This study aims to determine the effect of providing education through the TUNA (Telur untuk Anak / Eggs for Children) Innovation Program on the use of animal protein on improving the knowledge of health cadres. The method used was a pre-experimental design with a one-group pretest–posttest approach. The study sample consisted of 30 health cadres selected by total sampling. Data were collected using a knowledge questionnaire on the use of animal protein and egg processing as stunting prevention interventions, then analyzed using the Wilcoxon test. The results showed that before education, most cadres had a sufficient level of knowledge (46.7%), while after education, the majority of cadres were in the good knowledge category (83.3%), indicating the effect of providing TUNA Program education on improving cadre knowledge. Thus, the TUNA Innovation Program is effective as a strategy for empowering cadres in efforts to prevent stunting based on the use of animal protein.